How do you get this?:) let f(x)=(x+2)/(x+8) f^-1(-9)=?

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

How do you get this?:) let f(x)=(x+2)/(x+8) f^-1(-9)=?

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

you want the inverse of f(x)
\[f^(-1)(x) = -(2 (4 x-1))/(x-1)\]
the inverse is gotten suslly by switching x and y and resolves for y

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

You don't have to find the inverse, Just plug f(x)=-9, and then solve for x. That value of x is the inverse at x=-9.
let y = x+2 / x+8 yx + 8y = x+2 x(1-y) = 8y-2 x = (8y-2)/1-y which gives u d inverse now switch x and y and put in d value of x to get y
thank you!:)
x=(y+2)/(y+8) x(y+8)=y+2 xy +8x = y+2 xy - y = -8x +2 y(x-1) = -8x+2 y = (-8x+2) ------- (x-1)
y = (-8(-9)+2)/(-9-1) y = 74/-10 = -7.4
welll i did the very same
yay!! its verified then ;)
A simpler method, is to plug f(x)=-9 and then solve for x: \[-9={x+2 \over x+8} \implies -9x-72=x+2 \implies 10x=-74 \implies x=- 7.4\] So,\[f^{-1}(-9)=-7.4\]
I like my method :P
your method is just the same method rehashed lol
Haha, not really.
admit it, mine is better :P

Not the answer you are looking for?

Search for more explanations.

Ask your own question